Efektivitas Ekstrak Buah Bintaro (Cerbera manghas L.) dan Limbah Kulit Pisang sebagai Pestisida Nabati dan Pengkilap Aglaonema - Tania Amelya; Jidan Akbar; Sri Dewi Lestari; Abdul Hamid; Muhammad Hafizh; Lorenta In Haryanto (Lembaga Pengembangan Kinerja Dosen, 2023)
Aglaonema plants (Aglaonema spp.) are popular ornamental plants that are famous for the beauty and diversity of their leaves. However, pest attacks can disrupt the growth and beauty of this plant. An alternative to controlling pests is to use vegetable pesticides. This research aims to test the effectiveness of organic pesticides derived from bintaro fruit extract and the effect of using banana peels as a leaf polish on Aglaonema plants. Bintaro is a potential source of botanical pesticides because it contains compounds that inhibit insect feeding. On the other hand, banana peels, which are often overlooked, actually have the ability to naturally enrich the leaves because of their nutritional content. This research used a randomized block design (RAK) with six different treatments, including a control without treatment and chemical pesticide treatment as a comparison. The results of the study showed that bintaro fruit extract had no real effect on aglaonema pest attacks, P4 treatment had a real effect, with the highest number of respondents, but P3 treatment tended to give a duller leaf shine. These results show that the use of the botanical pesticide Bintaro fruit extract did not have a significant effect in killing Aglonema pests, but P2 and P3 treatments had a better effect than other treatments in dealing with pests and P4 treatment was the best in shining Aglonema leaves.